CGIAR Expert Finder: an ontology-based web tool for scouting expertise and partners - CGIAR Platform for Big Data in Agriculture (2019)
An Expert Finder prototype has been developed, to be demonstrated to Centers and made available to them for further improvements in 2020/2021.